Seleksi Generasi F2 untuk Mendapatkan Jagung dengan Kandungan Antosianin - Hari Isnaini Adrianto; Eries Dyah Mustikarini; Gigih Ibnu Prayoga (Institut Pertanian Bogor, 2021)
Purple corn is one type of corn plant with high anthocyanin content, which is good for health. Hybridization activities can obtain purple corn with anthocyanin content and yield power of 9.85 tons/ha with selection. This study aims to select F2 generation corn strains that have a purple color. The genetic materials were planted without replicated design. The lines used are derived from the F2 seed results of a cross between purple corn of Marassempulu and white corn of Magetan. There were 120 plant samples. The results showed about 24 lines that had purple seeds in the F2 generation. The selection results with a selection intensity of 50% obtained 12 lines of corn which could be continued for the next generation, namely F2-PxU11-14, F2-PxU11-20, F2-PxU11-21, F2-PxU6-15, F2-PxU11-2, F2-PxU6-16, F2-PxU11-13, F2-PxU11-11, F2-PxU6-5, F2-PxU6-8, F2-PxU11-6, and F2-PxU11-16. Kata kunci: corn, free-based, hybridization, purple, selection